Immunomodulatory Properties of Mesenchymal Stromal Cells: Still Unresolved “Yin and Yang” - Poggi, Alessandro; Zocchi, Maria R. (Current Stem Cell Research & Therapy, 2019)
Mesenchymal stromal cells (MSC) are mesodermal elements characterized by the ability to differentiate into several types of cells present mainly in connective tissues. They play a key function in tissue homeostasis and repair. Furthermore, they exert a strong effect on both innate and adaptive immune response. The main current of thought considers MSC as strong inhibitors of the immune system. Indeed, the first description of MSC immunomodulation pointed out their inability to induce alloimmune responses and their veto effects on mixed lymphocyte reactions. This inhibition appears to be mediated both by direct MSC interaction with immune cells and by soluble factors. Unfortunately, evidence to support this notion comes almost exclusively from in vitro experiments. In complex experimental systems, it has been shown that MSC can exert immunosuppressive effects also in vivo, either in murine models or in transplanted patients to avoid the graft versus host disease. However, it is still debated how the small number of administered MSC can regulate efficiently a large number of host effector lymphocytes. In addition, some reports in the literature indicate that MSC can trigger rather than inhibit lymphocyte activation when a very low number of MSC are co-cultured with lymphocytes. This would imply that the ratio between the number of MSC and immune cells is a key point to forecast whether MSC will inhibit or activate the immune system. Herein, we discuss the conflicting results reported on the immunomodulatory effects of MSC to define which features are relevant to understand their behavior and cross-talk with immune cells.
Keywords: immunosuppression